"Liquid Knife" to Fabricate Patterning Single‐Crystalline Perovskite Microplates toward High‐Performance Laser Arrays. Issue 19 (22nd March 2016) - Feng, Jiangang; Yan, Xiaoxu; Zhang, Yifan; Wang, Xuedong; Wu, Yuchen; Su, Bin; Fu, Hongbin; Jiang, Lei
Abstract : A facile and effective "liquid knife" is created by controlling the dewetting process of the liquid precursor, yielding patterning single‐crystalline perovskite microplates with uniform size, precise positioning, high quality, and low lasing thresholds. The sizes and location of single‐crystalline perovskite are controllable, leading to mode‐tunable lasing emission and patterned lasers.